LITERATUR REVIEW TENTANG PERAN BRAND AWARENESS DALAM MENINGKATKAN DAYA SAING BISNIS OPTIK LOKAL WILAYAH YOGYAKARTA TAHUN 2020 – 2025 - Wibowo, Arraywed Yudita; Kusumo, Sri Wahyu Budoyo; Wicaksono, Ardhitya Furqon (Jurnal Ekonomi Bisnis Manajemen dan Akuntansi (JEBISMA), 2025)
The development of the optical industry in Yogyakarta experienced significant acceleration between 2020 and 2025, driven by the adoption of digital technology and changes in consumer behavior. In this context, brand awareness has become a strategic factor in building the competitive advantage of local optical businesses. This study aims to evaluate the role of brand awareness in the competitiveness of local optical businesses in Yogyakarta using a Systematic Literature Review (SLR) and bibliometric approaches. A total of 38 articles from the Scopus, SINTA, and Google Scholar databases were analyzed using the PRISMA protocol and VOSviewer tool to map research trends, dominant keywords, and method distribution. The study results indicate that brand awareness significantly influences consumer loyalty, brand preference, and market differentiation. Quantitative approaches have been found to dominate in previous studies, but these are still limited to a more specific local context. This study concludes that strengthening brand awareness through a locality-based digital strategy is key to increasing the competitiveness of local optical businesses in Yogyakarta. Recommendations are provided for businesses to integrate local identity into their branding strategies.